Critical analysis of KIPAS counseling model: Professional counseling crisis phenomena by counselor in Indonesia - Irani, Luthfita Cahya (ProGCouns: Journal of Professionals in Guidance and Counseling, 2020)
The quality of counselor performance can be seen from the implementation of professional counseling that is complete and effective. On the other side, Indonesian counselors are struggling with Permendikbud No. 111 of 2014, which provides professional services at a ratio that approves a counselor serving 150 students. This makes it necessary for a counseling model that has a simpler, more concise procedure and immediately shows effective results accompanied by a load of cultural awareness in the implementation process. What has happened so far is that Indonesian counselors are still trapped in counseling models born from Western philosophy, not in accordance with the cultural, social and cultural diversity of Indonesia which often results in incomplete counseling processes. KIPAS counseling is a model of local culture-based counseling, making it effective to be applied in Indonesian counseling services. The reality that appears at this time is, the need for the amount of completion of the counseling implementation completely and effectively and is full of cultural understanding as the point of view of Indonesian counselors. This article uses a qualitative approach with a critical analytical method that aims to criticize the KIPAS counseling content that is reviewed based on the reality of the implementation of professional counseling by counselors inKeywords:professional counseling, KIPAS counseling model, counselor